Cortical thickness following electroconvulsive therapy in patients with depression: a longitudinal MRI study. (10th August 2019) - Gbyl, K.; Rostrup, E.; Raghava, J. M.; Carlsen, J. F.; Schmidt, L. S.; Lindberg, U.; Ashraf, A.; Jørgensen, M. B.; Larsson, H. B. W.; Rosenberg, R.; Videbech, P.
Abstract : Objective: Several studies have found an increase in hippocampal volume following electroconvulsive therapy (ECT), but the effect on cortical thickness has been less investigated. We aimed to examine the effects of ECT on cortical thickness and their associations with clinical outcome. Method: Using 3 Tesla MRI scanner, we obtained T1‐weighted brain images of 18 severely depressed patients at three time points: before, right after and 6 months after a series of ECT. The thickness of 68 cortical regions was extracted using Free Surfer, and Linear Mixed Model was used to analyze the longitudinal changes. Results: We found significant increases in cortical thickness of 26 regions right after a series of ECT, mainly within the frontal, temporal and insular cortex. The thickness returned to the baseline values at 6‐month follow‐up. We detected no significant decreases in cortical thickness. The increase in the thickness of the right lateral orbitofrontal cortex was associated with a greater antidepressant effect, r = 0.75, P = 0.0005. None of the cortical regions showed any associations with cognitive side effects. Conclusion: The increases in cortical thickness induced by ECT are transient. Further multimodal MRI studies should examine the neural correlates of these increases and their relationship with the antidepressant effect.